Understanding boundaries: A qualitative study on social stories as a preventive tool against inappropriate sexual behaviour in Asd Teenagers - Zulkefli, Mohd Yusof; Abdul Fuad, Ahmad Farid; Mohd Azman, Nur Aziemah; Tengku Mahamad, Tengku Elena; Khamis, Mohd Fadly (Journal of Islamic, Social, Economics and Development, 2025)
ASD teenagers commonly have difficulties in social understanding. Their emotional changes and increasing sexual urges may be delayed or prolonged. Moreover, families, therapists or caregivers are often concerned about the growing sexual behaviour in ASD teenagers. Therefore, this study aims to analyse the social story's impacts on controlling sexual behaviour among autism spectrum disorder (ASD) teenagers. The methodology used by the researchers in this study is the qualitative research method. Meanwhile, the case study served as the research design of this study. Fifteen participants were involved in this study. There are a few themes found in the triangulation data analysis. First, the findings show that the social story helped ASD teenagers to expect positive responses and adapt to social standards. Secondly, a social story is part of visual communication. It is another type of communication to convey a message. It also can be derived as a tool that can translate into effective communication. As for the recommendation of this study, the researchers would like to suggest that future researchers explore the integration between social stories and virtual learning. Secondly, the future researcher may conduct the research using experimental research. This research only narrates the impact and usefulness of the social story but lacks the figure to generalise the social story's impact explicitly.